Diagnostic tests in urology: magnetic resonance imaging (MRI) for the staging of prostate cancer. (15th January 2013) - Preston, Mark A.; Harisinghani, Mukesh G.; Mucci, Lorelei; Witiuk, Kelsey; Breau, Rodney H.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? The use of MRI for prostate cancer diagnosis and staging is increasing. Indications for prostate MRI are not defined and many clinicians are unsure of how best to use MRI to aid clinical decisions. This evidence‐based medicine article addresses the clinical utility of prostate MRI for preoperative staging. Based on a common patient scenario, a guide to calculating the probability of extraprostatic extension is provided.